Building a comics collection in the University of the Philippines Library a feasibility study - Cruz, Alvin Zernan R. (2004)
Comic books have been existed in the nimbus of pop culture since their conception. It is said that our national hero Dr. Jose Rizal drew the first cartoom strip tht saw publication here in the Philippines (Roxas, 1985). But the formal history of the Philippine komiks started in 1926 when Antonio S. Velasquez saw the potentials and possibilities of this medium.